Characterization of the karyotypic morphology of Haplopappus foliosus (Hook. & Arn.) (Asteraceae) - Marcelo Miranda-Cavallieri; Álvaro Solís-Céspedes; Paola Jara-Arancio; Cristian Villagra; Daniel Frías (Gayana: Botanica)
The characterization of the chromosomal morphology of Haplopappus foliosus (Hook. & Arn.) determined a chromosomal number of 2n = 10, with a karyotypic formula of one subtelocentric pair (st) and four submetacentric pairs (sm). The intrachromosomal asymmetry index (A1) and interchromosomal asymmetry index (A2) showed a moderate tendency towards telocentricity and low variability in the sizes of chromosome pairs.